Y yo…, ¿a quién lloro? Manifestaciones de duelo en el Jardín Cementerio Universal de Medellín, Colombia - Paola Stefanía Quintero Cardona; Claudia Lorena Gómez Sepúlveda; Mónica Johanna Giedelmann Reyes (Antípoda: Revista de Antropología y Arqueología, 2022)
Cemeteries are propitious settings in which to mourn the death of a loved one. Such expressions of grief have particular social logics associated with there being a corpse buried in the grave. But how is the relationship of the mourner transformed when there is no body as a result of a forced disappearance? Do the mourners’ interactions differ when there is an identified body as opposed to when there is not? Guided by these questions, Jardín Cementerio Universal de Medellín is presented as a space that unveils strategies used to deal with the complexity of mourning a loved one’s death. The purpose of this research is to demonstrate the manifestations of mourning present in graves with identified and unidentified bodies. To this end, an ethnographic exercise was conducted involving a qualitative analysis of funerary material culture and non-participant observation. The study documents the importance of having a physical space, the gravestone, where one can grieve the loss of a loved one. It is revealed that this space is especially relevant in the case of the indirect victims of forced disappearance, who go through complex mourning processes in the absence of a grave to hold their loved one’s body. In this case, the burial ground is a space that bears witness to the acts of violence that Colombia has suffered.